KEEFEKTIFAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE STAD MELALUI PEMANFAATAN ALAT PERAGA PADA MATERI LUAS LINGKARAN TERHADAP HASIL BELAJAR SISWA KELAS VI SDN 15 BENGKULU SELATAN SEMESTER I TAHUN PELAJARAN 2015/2016 - Sulasmi, Yuliar (Jurnal Math-UMB.EDU, 2016)
The problem of this research was is cooperative learning teaching model STAD type by using manipulatives more effective than conventional teaching model to study result especially comprehension aspect concept of students class VI first semester SDN 15 south Bengkulu school year 2015/2016 at area of a circle material. The objective of this research was to find out which one was more effective between Mathematic teaching  model cooperative learning STAD type by using manipulatives and conventional teaching model to study result in comprehension aspect concept of students class VI first semester SDN 15 south Bengkulu school year 2015/2016 at area of a circle material. The population of this research was the whole students of class VI first semester SDN 15 south Bengkulu school year 2015/2016. By using random sampling technique was elected class VIA as an experimental group anol class VIB as a control group, each groups consist of 20 students. The Experimental group was given teaching by using cooperative learning STAD treatment. While for the control group by using conventional learning treatment. Based on this research was found out that mean of experimental group = 66,45 and mean of a control group = 65,68. With n1 = 20 and n2 = 20 it was gained tobtain = 2,884. With equal evident 5% and dk= 78 it was gained ttable = 1,98. Because of tobtain ttable it could be concluded that mathematic teaching at sub material area of a circle with cooperative learning model STAD type by using manipulatives was better than conventional teaching and learning.                  Keywords: cooperative learning STAD type, using manipulatives, area of a circle.